Communication practices in global product development projects of Brazilian multinational firms (Revista de Administração, 2010)
This study sought to identify the most frequent and important communication practices used in the global product development projects of Brazilian multinationals and to analyze whether these communication practices vary according to certain project characteristics. The study has an exploratory nature and the research method chosen was the multiple case study. Our results indicate that the frequency of communication in global projects decreases as distance increases, making the control and coordination of the teams more difficult. However, distance, per se, despite adding to the challenges, does not necessarily cause communication problems, as one can bypass it with electronic communication tools. The study also concludes that communication practices and the importance ascribed to them vary depending on certain project characteristics, such as project type, product life cycle, project complexity and the integrative arrangements used in product development. Although these variations were identified, we found that communication practices do not arise in a standardized manner across all projects; conversely, they are improvised and circumstantial and do not rely on any specific planning at the beginning of the project.